High-sealing-performance packaging bag and preparation process thereof
By using a combination of polylactic acid, polycaprolactone, nano-silver filler composite antibacterial agent and epoxy-based compatible agent in the packaging bag, the problem of insufficient barrier properties of biodegradable packaging materials is solved, and high sealing and long Life-long packaging bags improve barrier and antibacterial properties.
Patent Information
- Application Number
- CN202411876998.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Biodegradable packaging materials have insufficient barrier properties in actual applications, resulting in short service life and are not suitable for packaging materials.
Using a combination of polylactic acid, polycaprolactone, nanosilver filler composite antibacterial agent and epoxy-based compatibility agent, the hybrid modified coating is loaded with nanosilver through the surface deposition of nano-2D filler and formed during the melt blending process. Chemical bonds improve interface effect and compatibility, and prepare high-sealing packaging bags.
It significantly improves the barrier properties and mechanical properties of the packaging bags, extends the service life, and enhances the antibacterial properties and barrier effects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging materials, and in particular relates to a high-sealability packaging bag and a preparation process thereof. Background Art
[0002] Compared with traditional packaging materials, biodegradable packaging materials have become a hot topic in the packaging field. Biodegradable packaging materials can play a positive role in ensuring food quality and safety and extending shelf life, and can also solve problems such as environmental pollution. However, due to the lack of barrier properties of biodegradable polymers in actual packaging applications, their application scope is greatly limited.
[0003] Patent application with publication number CN106750438A discloses an oxygen-barrier / water-barrier PBAT film material, in which a layer of prepolymer of a two-dimensional sheet material (montmorillonite) containing active groups is coated on the surface of the PBAT film by a solution curing method to obtain a water-barrier and oxygen-barrier composite material. This method significantly reduces the water vapor permeability, but in actual production and application, the coating is easily detached by external force, resulting in a short service life of the film, which is not suitable for packaging materials. Summary of the invention
[0004] The object of the present invention is to provide a highly airtight packaging bag and a preparation process thereof, so as to solve the problem of insufficient barrier properties of degradable packaging bags.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A highly airtight packaging bag comprises the following raw materials: polylactic acid, polycaprolactone, nano-silver filler composite antibacterial agent and epoxy compatibilizer; the mass ratio of the polylactic acid, polycaprolactone, nano-silver filler composite antibacterial agent and epoxy compatibilizer is 70-90:10-30:1-4:1-6; The nano silver filler composite antibacterial agent is a hybrid modified coating deposited on the surface of a nano two-dimensional filler and loaded with nano silver; the hybrid modified coating includes polydopamine and hyperbranched polyethyleneimine. The use of hyperbranched polyethyleneimine can accelerate the loading rate and loading capacity of silver, and combined with the excellent low viscosity and other properties of the hyperbranched polyethyleneimine itself, the dispersibility of the nano silver filler composite antibacterial agent is improved.
[0006] As a further preferred embodiment of the present invention, the nano two-dimensional filler is one of graphene oxide, molybdenum disulfide nanosheets, hexagonal boron nitride nanosheets and organic modified montmorillonite. Compared with one-dimensional nanomaterials, two-dimensional nanomaterials not only change the crystallinity of the substrate (polylactic acid, polycaprolactone), but also have a higher specific surface area and increase the path tortuosity, which can not only effectively reduce the gas permeability of nanocomposites, but also can be used as a carrier of materials such as antibacterial agents to give the packaging bag good antibacterial properties.
[0007] As a further preferred embodiment of the present invention, the epoxy compatibilizer includes oligomeric epoxy-terminated polysiloxane and epoxy vegetable oil. The epoxy compatibilizer can form chemical bonds between polylactic acid, polycaprolactone and nano silver filler composite antibacterial agent through chemical reaction during melt blending to enhance the interface effect and compatibility between the raw materials. The graft copolymer generated by the reaction is distributed at the interface between the two phases, which can improve the adhesion between the interfaces and play a significant role in increasing the volume, thereby improving the mechanical properties of the sample and giving full play to the barrier effect of the raw materials in use.
[0008] As a further preferred embodiment of the present invention, the oligomeric epoxy-terminated polysiloxane is obtained by hydrosilylation of terminal hydrogen silicone oil and allyl glycidyl ether at a molar ratio of 1:2.2; the epoxy vegetable oil includes one of epoxy soybean oil and epoxy castor oil. The use of oligomeric epoxy-terminated polysiloxane as an epoxy compatibilizer can not only enhance the interface effect and compatibility between the raw materials, but also the introduced silicon-oxygen chain segment has good toughness and hydrophobicity, which is beneficial to enhancing the mechanical properties and water vapor barrier properties of the sample.
[0009] As a further preferred embodiment of the present invention, the oligomeric epoxy-terminated polysiloxane is prepared by the following steps: The terminal hydrogen silicone oil and allyl glycidyl ether are mixed to obtain a reaction solution, and a catalyst is added at a temperature of 70-80°C, and the reaction is carried out at 85-90°C. The catalyst is an isopropanol solution containing 2% PtCl·6H2O. After the reaction is completed, the oligomeric epoxy-terminated polysiloxane is obtained by vacuum distillation.
[0010] As a further preferred embodiment of the present invention, the molecular weight of the hydrogen-terminated silicone oil is 500-600 g / mol. The molecular weight of the hydrogen-terminated silicone oil should not be too large. The larger the molecular weight, the higher the viscosity of the hydrogen-terminated silicone oil. The poor fluidity is not conducive to processing and affects the conversion rate of hydrosilylation.
[0011] A preparation process of a high-sealability packaging bag comprises the following steps: Dopamine and hyperbranched polyethyleneimine are used as raw materials, copolymerization reaction is carried out on the surface of nano two-dimensional filler, hybrid modified coating is deposited, and then nanosilver is loaded to obtain a nanosilver filler composite antibacterial agent; polylactic acid, polycaprolactone, nanosilver filler composite antibacterial agent and oligomeric epoxy-terminated polysiloxane are evenly mixed, granulated, and blown film to obtain a highly sealed packaging bag.
[0012] As a further preferred embodiment of the present invention, the nano silver filler composite antibacterial agent is prepared by the following steps: The specific steps are as follows: the nano two-dimensional filler and the dopamine solution are mixed, stirred at 30°C for 2-4h, centrifuged, the precipitate is vacuum dried at 60°C, added to the hyperbranched polyethyleneimine and silver nitrate solution, stirred at 30°C for 7-9h, centrifuged after the stirring, washed with water and vacuum dried at 60°C to obtain the nano silver filler composite antibacterial agent. Dopamine and hyperbranched polyethyleneimine are used as raw materials to form a hybrid modified coating on the surface of the nano two-dimensional filler. The hybrid modified coating includes polydopamine and hyperbranched polyethyleneimine. Polydopamine can be grafted with hyperbranched polyethyleneimine. Hyperbranched polyethyleneimine can improve the adsorption efficiency and adsorption capacity of silver. Polydopamine can be used as a reducing agent and protective agent to reduce silver ions into silver nanoparticles through its phenolic hydroxyl structure, and provide protection during the synthesis process to improve antibacterial stability.
[0013] The nano two-dimensional filler is first treated with polydopamine (dopamine as raw material). Polydopamine has excellent adhesion and can be used as a platform for secondary reactions. Therefore, the choice of raw materials is not limited, and suitable nano two-dimensional fillers can be selected based on usage scenarios and cost considerations.
[0014] As a further preferred embodiment of the present invention, the dopamine solution is a mixture of 0.5 g dopamine hydrochloride and 100 mL 10 mmol / L, pH=8.5 Tris-HCl buffer; the concentration of the silver nitrate solution is 50 mmol / L; The dosage ratio of the nano two-dimensional filler, the hyperbranched polyethyleneimine, the dopamine solution and the silver nitrate solution is 5g:0.3g-0.5g:100mL:100mL.
[0015] As a further preferred embodiment of the present invention, the temperatures of zones 1-4 during granulation are 120°C, 170°C, 185°C, and 175°C, and the screw speed is 40r / min; During the film blowing process, the temperatures of zones 1-4 were 160°C, 170°C, 185°C, and 170°C, and the screw speed was 30 r / min.
[0016] Beneficial effects of the present invention: The invention prepares a highly airtight packaging bag and discloses a preparation process thereof. In the invention, polylactic acid and polycaprolactone are used as main substrates, and the high mechanical strength of polylactic acid and the excellent flexibility of polycaprolactone are utilized to give the packaging bag good mechanical properties. The invention also adds a nano silver filler composite antibacterial agent and an epoxy compatibilizer, wherein the nano silver filler composite antibacterial agent uses nano two-dimensional fillers as raw materials, and the nano two-dimensional fillers have a high aspect ratio and can block the penetration of gas molecules, and are combined with an epoxy compatibilizer (reactive compatibilizer) to improve the dispersion performance, thereby further improving the barrier performance and mechanical properties of the packaging bag. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Preparation Example Preparation of oligomeric epoxy-terminated polysiloxane: The terminal hydrogen silicone oil and allyl glycidyl ether are mixed in a molar ratio of 1:2.2 to obtain a reaction solution. At a temperature of 80° C., a catalyst is added in a ratio of 60 mg per liter of the reaction solution. The reaction is carried out at 85° C. for 3 hours. The catalyst is an isopropanol solution containing 2% PtCl·6H2O. After the reaction is completed, the oligomeric epoxy-terminated polysiloxane is obtained by vacuum distillation. The molecular weight of the terminal hydrogen silicone oil is 500-600 g / mol.
[0019] Example 1-Example 10 The preparation of a highly airtight packaging bag comprises the following steps: Dopamine and hyperbranched polyethyleneimine are used as raw materials, copolymerization reaction is carried out on the surface of nano two-dimensional filler, hybrid modified coating is deposited, and nanosilver is loaded to obtain a nanosilver filler composite antibacterial agent; the specific steps are as follows: according to the proportion, 5g of graphene oxide and 100mL of dopamine solution are mixed, stirred at 30℃ for 2-4h, centrifuged, and the precipitate is vacuum dried at 60℃, 0.3-0.5g of hyperbranched polyethyleneimine (average M n ~10,000, purity 99%) and 100mL 50mmol / L silver nitrate solution are mixed, and the above precipitate is added, and stirred at 30°C for 7-9h. After stirring, centrifugation is performed, and the mixture is washed with water and vacuum dried at 60°C to obtain a nano-silver filler composite antibacterial agent. The dopamine solution is prepared by mixing 0.5g dopamine hydrochloride with 100mL 10 mmol / L, pH=8.5 Tris-HCl buffer.
[0020] Polylactic acid, polycaprolactone, nano silver filler composite antibacterial agent and epoxy compatibilizer are mixed in a mass ratio of 70-90:10-30:1-4:1-6 as shown in Table 1; granulated and blown film to obtain a highly sealed packaging bag, wherein the epoxy compatibilizer in Examples 1 to 9 is the low molecular weight epoxy-terminated polysiloxane prepared in the preparation example, and the epoxy compatibilizer in Example 10 is epoxy soybean oil. During the granulation process, the temperature of zones 1-4 is 120°C, 170°C, 185°C, and 175°C, and the screw speed is 40r / min. During the film blowing process, the temperature of zones 1-4 is 160°C, 170°C, 185°C, and 170°C, and the screw speed is 30r / min.
[0021]
[0022] The samples prepared in Example 1 to Example 10 were tested. The mechanical property test was based on GB / T 1040.2-2022. Five parallel samples were selected for each sample, and the average value of the five times was calculated as the experimental result.
[0023] When testing oxygen permeability, select 3 parallel samples for each sample and use them after balancing for 24 hours in an environment of 23±2℃ and 50%RH. According to the national standard GB / T 1038.1-2022, test method for gas permeability of plastic films and sheets, the oxygen permeability coefficient of the film is measured by the pressure difference method, unit: cm 3 cm / (cm 2 ·s·Pa). The size of the sample is 120mm×120mm.
[0024] When testing the moisture permeability, select 3 parallel samples for each sample, and measure the moisture permeability of the film according to the national standard GB / T1037-2021. Use cup weight gain, set the temperature to 38°C, and the humidity to 90%. Take it out every 24 hours, and weigh it after balancing for 30 minutes. Maintain a certain water vapor pressure difference on both sides of the sample, test the mass of water vapor passing through the sample, and calculate the water vapor permeability coefficient (moisture permeability coefficient), unit: g·cm / (cm 2 ·s·Pa).
[0025] The antibacterial performance was tested using the ASTM E2180-07 standard method, by adding 40 μL of 10 8CFU / mL bacterial solution (Escherichia coli was selected as the strain), the surface was covered with a sterile glass slide, and all samples were cultured in a culture dish (35mm in diameter) at 37°C for 1h. Then the glass slide and the film surface were rinsed with 3.6mL of PBS, and a series of dilutions were performed, and finally the live bacterial colonies were counted, 37°C, cultured for 24h, and each test was repeated 3 times. The blank group was a composite antibacterial agent without adding nanosilver filler and epoxy compatibilizer. Antibacterial rate = (blank group colony count - sample group colony count) / blank group colony count × 100%. The test results are shown in Table 2 below:
[0026] According to the test results recorded in Example 1-Example 3, the test sample prepared by polylactic acid and polycaprolactone in a mass ratio of 80:20 has good mechanical properties and the best comprehensive performance. According to the test results recorded in Example 4-Example 10, adjusting the amount of nanosilver filler composite antibacterial agent and epoxy compatibilizer in the material can optimize the barrier performance (oxygen permeability and moisture permeability). Among them, increasing the amount of nanosilver filler composite antibacterial agent is beneficial to improving the mechanical properties and barrier properties of the sample, but the enhancement is limited. Combined with the data of Example 4-Example 5, it can be seen that too much nanosilver filler composite antibacterial agent is prone to agglomeration and it is difficult to form a good uniform and dispersed state in the matrix, resulting in a decrease in the tensile strength of the sample, and the elongation at break gradually decreases with the increase in the amount of nanosilver filler composite antibacterial agent. In Example 6-Example 8, with the increase in the amount of epoxy compatibilizer, the tensile strength shows a trend of first increasing and then decreasing. Among them, in Example 7, various properties reach a relatively good level. The addition of epoxy compatibilizer is conducive to improving the dispersibility of the filler. The reason for the reduction is that the compatibility of the system increases, the dispersed molecules are more evenly arranged, resulting in reduced crystallization, which further improves the mechanical properties. In Example 9, the amount of nanosilver filler composite antibacterial agent and epoxy compatibilizer was further increased, the tensile strength increased to a limited extent, and the elongation at break showed a downward trend. In Example 10, epoxy soybean oil was selected as the epoxy compatibilizer, and the mechanical properties decreased slightly. There was a large difference in the data of the moisture permeability coefficient. The reason is that the epoxy compatibilizer belongs to a reactive compatibilizer. The silicon oxygen segment in the structure of the oligomeric epoxy-terminated polysiloxane is introduced into the system of the sample, which is conducive to improving the flexibility and hydrophobicity of the sample. Compared with epoxy soybean oil, it can better hinder the penetration of water molecules, thereby improving the moisture barrier performance.
[0027] Comparative Example 1 Compared with Example 7, in this comparative example, no hyperbranched polyethyleneimine was added during the preparation of the nano-silver filler composite antibacterial agent, and the other raw materials and the preparation process remained unchanged.
[0028] Comparative Example 2 Compared with Implementation 7, this comparative example differs in that the amount of raw materials is adjusted, and the mass ratio of polylactic acid, polycaprolactone, nano-silver filler composite antibacterial agent and epoxy compatibilizer is 80:20:8:5, and the other raw materials and preparation process remain unchanged.
[0029] The relevant properties of the samples prepared in Comparative Example 1-Comparative Example 2 were tested, and the results are shown in Table 3 below:
[0030] According to the test results recorded in Example 7 and Comparative Examples 1-2, the addition of hyperbranched polyethyleneimine in the process of preparing the nano-silver filler composite antibacterial agent is conducive to improving the performance of the sample, wherein the structure of the hyperbranched polyethyleneimine exhibits characteristics such as low viscosity, which is conducive to improving the dispersibility of the nano-silver filler composite antibacterial agent. In addition, the hyperbranched polyethyleneimine has a strong adsorption capacity for anions, which is manifested as an improvement in the antibacterial effect. Further increasing the proportion of the nano-silver filler composite antibacterial agent is not conducive to improving the performance.
[0031] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A highly airtight packaging bag, characterized in that: The invention comprises the following raw materials: polylactic acid, polycaprolactone, nano silver filler composite antibacterial agent and epoxy compatibilizer; the mass ratio of the polylactic acid, polycaprolactone, nano silver filler composite antibacterial agent and epoxy compatibilizer is 70-90:10-30:1-4:1-6; The nano silver filler composite antibacterial agent is a hybrid modified coating deposited on the surface of a nano two-dimensional filler and loaded with nano silver; the hybrid modified coating comprises polydopamine and hyperbranched polyethyleneimine.
2. A highly airtight packaging bag according to claim 1, characterized in that: The nano two-dimensional filler is one of graphene oxide, molybdenum disulfide nanosheets, hexagonal boron nitride nanosheets and organic modified montmorillonite.
3. A highly airtight packaging bag according to claim 1, characterized in that: The epoxy compatibilizer includes oligomeric epoxy-terminated polysiloxane and epoxy vegetable oil.
4. A highly airtight packaging bag according to claim 3, characterized in that: The oligomeric epoxy-terminated polysiloxane is obtained by hydrosilylation of hydrogen-terminated silicone oil and allyl glycidyl ether in a molar ratio of 1:2.2; the epoxy vegetable oil includes one of epoxy soybean oil and epoxy castor oil.
5. A highly airtight packaging bag according to claim 4, characterized in that: The oligomeric epoxy-terminated polysiloxane is prepared by the following steps: The terminal hydrogen silicone oil and allyl glycidyl ether are mixed to obtain a reaction solution, and a catalyst is added at a temperature of 70-80°C, and the reaction is carried out at 85-90°C. The catalyst is an isopropanol solution containing 2% PtCl·6H2O. After the reaction is completed, the oligomeric epoxy-terminated polysiloxane is obtained by vacuum distillation.
6. A highly airtight packaging bag according to claim 4, characterized in that: The molecular weight of the hydrogen-terminated silicone oil is 500-600 g / mol.
7. A process for preparing a highly airtight packaging bag as claimed in any one of claims 1 to 6, characterized in that: The steps include: Dopamine and hyperbranched polyethyleneimine are used as raw materials, copolymerization reaction is carried out on the surface of nano two-dimensional filler, hybrid modified coating is deposited, and then nanosilver is loaded to obtain a nanosilver filler composite antibacterial agent; polylactic acid, polycaprolactone, nanosilver filler composite antibacterial agent and oligomeric epoxy-terminated polysiloxane are evenly mixed, granulated, and blown film to obtain a highly sealed packaging bag.
8. The process for preparing a highly airtight packaging bag according to claim 7, characterized in that: The nano silver filler composite antibacterial agent is prepared by the following steps: The specific steps are as follows: mix the nano two-dimensional filler and dopamine solution, stir at 30°C for 2-4 hours, centrifuge, vacuum dry the precipitate at 60°C, add hyperbranched polyethyleneimine and silver nitrate solution, stir at 30°C for 7-9 hours, centrifuge after stirring, wash with water and vacuum dry at 60°C to obtain a nano silver filler composite antibacterial agent.
9. The process for preparing a highly airtight packaging bag according to claim 8, characterized in that: The dopamine solution is prepared by mixing 0.5 g dopamine hydrochloride with 100 mL 10 mmol / L Tris-HCl buffer solution with a pH of 8.5; the concentration of the silver nitrate solution is 50 mmol / L; The dosage ratio of the nano two-dimensional filler, the hyperbranched polyethyleneimine, the dopamine solution and the silver nitrate solution is 5g:0.3g-0.5g:100mL:100mL.
10. The process for preparing a highly airtight packaging bag according to claim 7, characterized in that: During the granulation process, the temperatures of zones 1-4 were 120°C, 170°C, 185°C, and 175°C, and the screw speed was 40 r / min; During the film blowing process, the temperatures of zones 1-4 were 160°C, 170°C, 185°C, and 170°C, and the screw speed was 30 r / min.
Citation Information
Patent Citations
Water / oxygen barrier polymer-based composite material as well as preparation method and application thereof
CN106750438A
Polylactic acid composite material and preparation method thereof
CN103113730A
Production method for cation ultraviolet light curing frame glue used for organic electroluminescence displayer
CN104946186A
Biodegradable supertough polylactic acid (PLA) blend material and preparation method thereof
CN105860468A
Biocompatible polymer capable of crosslinking, having improved elasticity and elongation, and shape memory properties, and preparation method and use thereof
WO2024172476A1
Cited By
Degradable antibacterial plastic packaging bag and preparation method thereof
CN120365716A
Degradable antibacterial plastic packaging bag and preparation method thereof
CN120365716B
High-barrier antibacterial packaging material, preparation method thereof and packaging bag
CN120699402A